2011
DOI: 10.1038/onc.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of an intronic region regulates miR-199a in testicular tumor malignancy

Abstract: In the testicular cancer cell line, NT2, we previously demonstrated that differentially methylated regions were located in introns or intergenic regions, and postulated these might regulate non-coding RNAs. Three micro-RNAs and three small nucleolar RNAs were differentially methylated; one, miR-199a, was associated with the progression and prognosis of gastric and ovarian cancers. In this report we document, by epigenomic profiling of testicular tissue, that miR-199a is transcribed as antisense of dynamin 3 (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 44 publications
3
125
0
Order By: Relevance
“…miR-107, a miR down-regulated by hypoxia, attenuates cell migration (37,38) and blocks VEGF-dependent angiogenesis by targeting hypoxia-inducing factor (HIF)-1␤ (39). The current study, together with findings from previous reports, reinforces the concept that miR-199a-5p not only inhibits cell migration (9,13,16) but also exerts potent angiostatic effect on endothelial cells by targeting a discrete subset of gene(s).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…miR-107, a miR down-regulated by hypoxia, attenuates cell migration (37,38) and blocks VEGF-dependent angiogenesis by targeting hypoxia-inducing factor (HIF)-1␤ (39). The current study, together with findings from previous reports, reinforces the concept that miR-199a-5p not only inhibits cell migration (9,13,16) but also exerts potent angiostatic effect on endothelial cells by targeting a discrete subset of gene(s).…”
Section: Discussionsupporting
confidence: 72%
“…It is expressed in a variety of organs including the brain (6), liver (9), stomach (10), ovarian tissue (11,12), testicular tissue (13), and the cardiovascular system, such as in cardiomyocytes (7,8) and endothelial cells (14,15). Recent evidence revealed that miR-199a-5p plays a critical role in attenuating cell migration and in limiting cancer cell metastasis by targeting receptor tyrosine kinase Discoidin domain receptor-1 (9), Axl (16), and anti-adhesive transmembrane glycoprotein podocalyxin-like protein 1 (13). We hypothesized that miR-199a-5p exerts angiostatic effects on endothelial cells.…”
mentioning
confidence: 99%
“…12,21,40 Another recent study showed that miR-199a-5p expression was upregulated in mice with idiopathic pulmonary fibrosis (IPF), suggesting that miR-199a-5p could regulate tissue fibrosis in different types of fibroproliferative diseases. 41 MiR-199a-5p can also regulate cardiomyocyte size during cardiac hypertrophy under ischemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that several miRNAs, including miR-34b/c, miR-129, miR-137, miR-181C, miR-199a, miR-212, miR-512 and miR-516, were dysregulated and showed aberrant methylation patterns in gastric cancer cells. 6,9,[14][15][16][17][18][19][20][21] The three pri-miR-9 transcripts are all located within non-protein coding transcripts (Fig. 2A).…”
Section: Cell Lines and 5-aza-dc Treatmentmentioning
confidence: 99%